Specialization in sports: A theoretical approach - Wunderlich, A. C.; Follert, F.; Daumann, F. (PLOS ONE, 2021)
Nations have been competing in sporting competitions for centuries. Therefore, explaining the success of different countries has a long history in sports science. At first, researchers tried to explain success patterns with the help of divergent geographical factors. Later, literature included other determinants on the macro-level which provide evidence that especially the GDP as a proxy for the prosperity of a country has a significant impact on success in sports. Within this broader field of research, also specialization patterns in sports developed into an important topic of research. In line with the literature on factors which lead to (national) success, so far, the discussion mostly concentrates on determinants on a macro-level. We identify the problem that different specialization patterns can be observed in countries that have similar factors on the macro-level, as well. There seems to be a research gap concerning the influencing factors on a meso-level. As a result, the aim of this paper is to show which determinants on the meso-level can affect sports specialization patterns. We provide a model based on the findings of lobbying theory that explains not only different specialization patterns between, e.g., Europe and Africa, but also different specialization patterns within a continent and dissimilar patterns of countries with a similar macro-level can be understood. Overall, our paper contributes to the discussion on specialization in elite sports from an economic perspective, so that future research can build on our work, in particular concerning empirical tests of our approach.